A two-phase procedure for a multi-objective programming problem with fuzzy coefficients based on group decision making for project selection - Eren, Miraç (Croatian Operational Research Review, 2017)
Regional Development Agencies (RDAs) play a major role in ensuring sustainability and reducing inter-regional and intra-regional development disparities in line with the principles and policies set in the National Development Plan and Programs. This is done by enhancing cooperation among the public and private sectors, as well as non-governmental organizations. To achieve these targets, RDAs use certain tools such as financial support programs, technical support programs, and the like. Accordingly, an effective evaluation mechanism is crucial in selecting projects that have more added value and higher multiplier effects. In this regard, determining the right parameters that assist in choosing the best projects should be clearly demonstrated. In this study, the selection of projects according to the evaluating criteria of support mechanisms considered by RDAs are discussed through the procedure provided by a practical solution methodology, which is an integration of fuzzy parametric programming (FPP) and fuzzy linear programming (FLP). Later, a two-phase procedure is introduced to solve multi-objective fuzzy linear programming problems.